Analysis of the Hindfoot Alignment Measured in 3D After a Medializing Calcaneal Osteotomy Using a Pre- and Postoperative Weightbearing CT. Issue 3 (14th September 2018) - Burssens, Arne; Barg, Alexej; Leenders, Timothy; Clockaerts, Stefan; Burssens, Peter; Victor, Jan
Category: Hindfoot Introduction/Purpose: An adult acquired flat foot (AAFD) is a complex 3D deformity. A medializing calcaneal osteotomy (MCO) is a surgical procedure frequently performed to correct the valgus alignment of the hindfoot in a stage II AAFD, when conservative measurements fail. However currently little is known on its accurate influence regarding the hindfoot alignment (HA). The aim is therefore to assess the influence of a MCO on the 3D HA using computer aided software analysis of the images retrieved from a weightbearing cone beam CT (WBCT). Methods: Twelve patients with a mean age of 49, 4 years (range 18-67yrs) were prospectively included in a pre-post study design. Indications for surgical correction by a MCO with a solitary translation consisted of an AAFD stage II (N=10) and a posttraumatic valgus deformity (N=2). Fixation of the osteotomy was performed by a step-plate or double screw. WBCT was obtained pre- and post-operative. Images were subsequently segmented to allow a HA calculation in 3D(HA3D) by an angle between the anatomical tibia axis and the axis connecting the computed inferior calcaneuspoint and the centroid of the talus in the coronal plane based on a Cartesian coordinatesystem(Fig 1A, C). The tibia in the HA3D was separately assessed by the anatomical tibia axis (TAx 3D) and the axis to determine the tibial rotation(TR 3D) in the axial plane by connecting the computed most outer point of the anterior and posterior tubercle of the incisura fibularis(Fig 2A, D). Results: The mean medial translation of the calcaneal osteotomy during surgery was 5.72 mm (SD = 3.9). The mean HA3D pre-operatively equaled 18.21 degrees of valgus (SD = 6.6) and post-operatively 9.31 degrees of valgus (SD = 6.18). The Paired Student's t-test showed a significant correction of 8.89 degrees (95%CI [5.99, 11.80], P<0.001). The mean TAX 3D pre-operatively was 6.80 degrees of valgus (SD = 3.38) and post-operatively 4.11 degrees of valgus (SD = 2.77), with a significant difference of 2.69 degrees (95%CI [1.79, 3.59], P <0.001). The mean TR3D pre-operatively was -27.11 degrees (SD = 4.77) and post-operatively - 28.80 degrees (SD = 5.98) and showed a significant difference of 1.69 degrees (95%CI [0.41, 2.97], P = 0, 016). Conclusion: This study shows an effective correction of the valgus hindfoot in an AAFD. It appears that the correction is not only situated in the calcaneus but also to a lesser extent in the tibia and this resulted in 15% of the achieved HA correction. The novelty is the 3D weightbearing assessment of a hindfoot correction and the shown influence on the tibia. This information could be of use to take in to account when performing a pre-operative planning of a hindfoot deformity.